Buck Converter Control for Lead Acid Battery Charger using Peak Current Mode - Asep Nugroho; Estiko Rijanto; Latif Rozaqi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
DC-DC buck converters are used for battery chargers in many applications including renewable energy sources, inverters, electric vehicles and robots. In this paper a buck converter was built and its controller was developed using peak current control mode for current loop and phase lag for voltage loop. This paper proposes a formulation of plant disturbance due to load variation to obtain a nominal model based on small signal approach. The controller was derived analytically based on the nominal model. Experiment results show that the buck control system functions well in regulating the output voltage. During the start up without any load it can reduce input voltage from 300 V to output voltage of 133.9 V in 19.3 ms. The developed controller can maintain the output voltage under load variation from no load to sudden load of 0.26 A. When it was implemented to charge a lead acid battery string, constant current of 3.36 A was charged in the first 173 minutes followed by constant voltage of 134.7 V until the end of charging at time 483 minutes. Thus, the developed control system of lead acid battery charger works well.